2007
DOI: 10.1111/j.1745-7254.2007.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative growth inhibition of human gastric adenocarcinoma treated with a combination of celecoxib and octreotide

Abstract: Aim: To gain insight into the histopathological responses and molecular targets in the inhibition of growth of human gastric cancer treated with celecoxib (a cyclooxygenase [COX]‐2 inhibitor) combined with octreotide. Methods: Seventy five patients with gastric cancer undergoing curative gastrectomy or extended resection were randomly divided into 3 groups. The apoptosis of tumor cells was measured by terminal deoxynucleotide transferase‐mediated dUTP nick end‐labeling (TUNEL) assay. Gastric cancer microvessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Many studies have shown that COX-2 is involved in inhibition of apoptosis, potentiation of cell growth, and angiogenesis in familial adenomatous polyposis, esophageal cancer, gastric cancer, lung cancer, and urinary bladder cancers, etc., and as such is a target for drug development of selective COX-2 inhibitors [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that COX-2 is involved in inhibition of apoptosis, potentiation of cell growth, and angiogenesis in familial adenomatous polyposis, esophageal cancer, gastric cancer, lung cancer, and urinary bladder cancers, etc., and as such is a target for drug development of selective COX-2 inhibitors [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rofecoxib and octreotide were found to have synergic antineoplastic effects in vitro in SGC-7901 cells (a gastric cancer cell line) and in xenografts in nude mice [17], and human gastric adenocarcinoma growth was found to be inhibited preoperatively by a combination of celecoxib and octreotide [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found out that the accuracy of IC PAT in identifying SI was 9.5–11.2% higher than the conventional CT examination [6]. We speculated that effective NAC could reduce IC PAT by inhibiting the growth of blood vessels in gastric serosa and surrounding fat tissues [24, 25]. Moreover, we attempted to explore the diagnosis value of IC PAT in identifying post-NAC SI in AGC patients.…”
Section: Discussionmentioning
confidence: 99%